2015
DOI: 10.1126/scisignal.2005667
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TRPV1 channels inhibits mechanosensitive Piezo channel activity by depleting membrane phosphoinositides

Abstract: Capsaicin is an activator of the heat-sensitive TRPV1 (transient receptor potential vanilloid 1) ion channels and has been used as a local analgesic. We found that activation of TRPV1 channels with capsaicin either in dorsal root ganglion neurons or in a heterologous expression system inhibited the mechanosensitive Piezo1 and Piezo2 channels by depleting phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] and its precursor PI(4)P from the plasma membrane through Ca2+-induced phospholipase Cδ (PLCδ) activation. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
178
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(202 citation statements)
references
References 60 publications
12
178
1
Order By: Relevance
“…However, our analysis has not been exhaustive as we did not examine all splice variants of Piezo2 and we did not investigate the potential interaction of Piezo2 with other membrane proteins. Other intracellular signaling pathways (Borbiro et al, 2015;Dubin et al, 2012) and protein interactions (Narayanan et al, 2016;Poole et al, 2014) have been shown to modulate Piezo2 function. More importantly, to fully appreciate the contribution of receptor diversification, it will be important to determine the in vivo consequences of Piezo2 splicing.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis has not been exhaustive as we did not examine all splice variants of Piezo2 and we did not investigate the potential interaction of Piezo2 with other membrane proteins. Other intracellular signaling pathways (Borbiro et al, 2015;Dubin et al, 2012) and protein interactions (Narayanan et al, 2016;Poole et al, 2014) have been shown to modulate Piezo2 function. More importantly, to fully appreciate the contribution of receptor diversification, it will be important to determine the in vivo consequences of Piezo2 splicing.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data does not argue that other factors are not involved in modulating Piezo mechanosensitivity. For example, cytoskeleton and associated proteins such as STOML3 regulate the mechanosensitivity of Piezo1 (Borbiro et al, 2015;Gottlieb et al, 2012;Poole et al, 2014). Regardless, our studies establish that like the bacterial MS channels, the mechanosensitivity of Piezo1 is inherent, and no other proteins or second messenger signals are required for the baseline mechanosensitivity of Piezo1.…”
Section: Activation Of Piezo1 By Solvent Injection Assaymentioning
confidence: 84%
“…The fi ndings from Borbiro et al (7) uncover part of the underlying mechanisms of capsaicin-induced attenuation in mechanical pain, which employs a TRPV1-mediated calcium infl ux that triggers depletion of phosphoinositides. Given the fi ndings from Patapoutian's group indicating that Piezo2 does not account for painful mechanosensation (8), further study is required to confi rm this inhibitory effect in vivo and ascertain which Piezo channel subtype is regulated in hyperalgesic states.…”
mentioning
confidence: 95%
“…In this issue of Science Signaling, Borbiro et al (7) demonstrate that activation of TRPV1 inhibits rapidly adapting, mechanically activated (MA) cation channels. They report that the majority (>70%) of TRPV1-positive neurons exhibit rapidly adapting, intermediate, or slowly adapting MA current.…”
mentioning
confidence: 97%
See 1 more Smart Citation